Real Exchange Rate Levels, Productivity and Demand Shocks : Evidence from a Panel of 14 Countries - Johnston, Louis (IMF Working Papers; Working Paper ;, 1997)
We investigate the long-run relationship between the real exchange rate, traded and nontraded productivity levels, and government spending for 14 OECD countries, using recently developed panel cointegration tests. The results indicate that under certain assumptions it is easier to detect cointegration in panel data than in the available time series; moreover, the rate of reversion to long-run equilibrium is estimated with greater precision. Using the model augmented by oil prices, we find that in 1991 (the last year productivity data are available) there is less overvaluation of the U.S. dollar than that implied by a naive version of purchasing power parity.